Epidemiology of talus fractures in Finland: a nationwide register study from 1997 to 2020 - Evgenii Brushtein; Nikke Partio; Tuomas T. Huttunen; Jussi P. Repo; Heikki Mäenpää; Ville M. Mattila (BMC Musculoskeletal Disorders)
Abstract Background The aim of this study was to estimate the nationwide incidence of talus fractures (per 100 000 person-years) and to determine the incidence of operative treatment in the Finnish population. Methods Based on Finnish Care Register for Health Care data, all patients 18 years and older admitted to hospital with talar fractures between 1997 and 2020 were included. Results During the 24-year study period, 5247 patients with primary or secondary diagnoses of talar fracture were identified. The mean incidence during the whole study period was 50.4 per 100 000 person-years. There was a clear increase starting from the year 2009 (61.4 per 100 000 person-years), that continued and the incidence in 2018 raised up to 106.8 person-years. The total incidence of operations performed on talar fractures remained almost the same during the study period (9.1 per 100 000 person-years from 1997 to 2020). Conclusions While the incidence of performed operations had remained stable, the incidence of talar fractures in Finland has increased during the last decades. The increase was more prominent in men. The observed change is possibly due to the progress and availability of computer tomography. Level of Evidence III